Symmetry does not indicate recovery: Single-leg hop before and after a lower extremity injury - Simon, J. E.; Yom, J.; Grooms, D. R. (International Journal of Sports Medicine, 2021)
Current recommendations for return-to-play decision-making involve comparison of the injured limb to the uninjured limb. However, the use of the uninjured limb as a comparison for hop testing lacks empirical evidence. Thus, the purpose of this study was to determine the effects of lower extremity injury on limb symmetry and performance on the single-leg hop for distance. Two-hundred thirty-six adolescent athletes completed the single-leg hop for distance before the beginning of the season (pre-injury). Forty-four adolescent athletes sustained a lower extremity injury (22 ankle and 12 knee) and missed at least three days of sports participation. All individuals had completed the single-leg hop for distance before the beginning of the season (pre-injury) and at discharge (post-injury). Injured limb single-leg hop for distance significantly decreased at return-to-play from pre-injury with a mean decrease of 48.9 centimeters; the uninjured limb also significantly decreased, with a mean decrease of 33.8 centimeters. Limb symmetry did not significantly change pre- to post-injury with a mean difference of 1.5%. Following a lower extremity injury, single-leg hop for distance performance degrades not only for the injured limb but also the uninjured limb. However, limb symmetry did not change following a lower extremity injury.